Three-layer Repair Coating System for Manholes, Pump Stations, and Tanks in Aggressive Sulfate Environment - Pawlak, Tomasz Grzegorz; Szymczak-Graczyk, Anna; Garbowski, Tomasz (Civil and environmental engineering reports, 2025)
Advancements in the repair and protection of water and wastewater infrastructure are now focused on using an innovative material called polyurea. Distinguished by its rapid curing time and versatile applications, polyurea is applied using a spray gun with high-pressure pumps. The introduction of new building materials is part of ongoing efforts to meet stringent environmental, health, and performance standards, and polyurea offers significant improvements by eliminating solvents and volatile organic compounds (VOCs). This paper presents a technological protocol starting with inspection and cleaning, followed by drying, and ending with the application of three layers: a moisture-blocking base layer, a rigid polyurethane middle layer for structural reinforcement, and a final sealing and anti-corrosion layer. This innovative method ensures a homogeneous, seamless structure, enhances construction durability, and accelerates the repair process, allowing immediate resumption of operation. Designed specifically for aggressive wastewater environments, this system is characterized by excellent corrosion resistance, making it ideal for water and wastewater infrastructure elements such as reinforced concrete manholes, sewage pumping stations, and tanks. Customizable polyurea properties allow personalization based on environmental aggressiveness, structure size, and abrasion resistance, representing a significant advancement in infrastructure maintenance technology. The paper showcases this modern repair and renovation method, highlighting its applications, benefits, and potential to revolutionize water and wastewater infrastructure maintenance in challenging conditions. The effectiveness of this solution is also compared with traditional methods, demonstrating the superiority of the three-layer system in terms of waterproofing, sulfuric acid resistance, monolithic structure, and application time.